PEMAHAMAN HISTORIS SISWA TERHADAP BAHASA INDONESIA SEBAGAI BAHASA PERSATUAN: STUDI LAPANGAN DALAM PEMBELAJARAN SEJARAH - Manda Putri Berutu; Aurel Putri Azahra; Muhhamad Fahrezi; Meiman Harefa; Nadra Amalia (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Indonesian holds a vital role as a unifying language capable of uniting Indonesia’s diverse society, which comprises various ethnic groups, cultures, and regional languages. Therefore, a historical understanding of the birth and development of Indonesian needs to be instilled in students through history learning. This study aims to determine the level of students’ historical understanding of Indonesian as a unifying language and to analyze the role of history learning in fostering a sense of nationalism and national identity. The research employed a quantitative descriptive method involving 11th-grade students of SMA Negeri 7 Medan as the research subjects. Data were collected through a digital quiz consisting of 25 multiple-choice questions related to the history of Indonesian, the role of the Youth Pledge, the development of the language, and the functions of Indonesian in the life of the nation and state. The data were analyzed using descriptive statistical techniques based on the accuracy of answers and student learning outcomes. The results showed that students’ historical understanding was in the good category. Most students were able to explain the background of the birth of Indonesian, understand the role of the Youth Pledge in establishing the unifying language, and recognize the functions of Indonesian as a symbol of national identity and a tool for national unity. Furthermore, the use of digital quizzes was proven to increase student participation and motivation in history learning. Thus, history learning contributes to strengthening historical awareness, a sense of nationalism, and appreciation for Indonesian as the nation’s identity.